(untitled) (Current Horticulture, 2024)
Non-traditional ornamentals are under-utilized and un-explored plant species or relatives of commercially important crops having attractive ornamental plant characteristics, but its potential ornamental value is not fully realized and primarily not recognized or treated as an ornamental/floriculture crops. A number of commercially important fruit crops, plantations, vegetables, spices, and aromatic have a huge number of wild relatives, which cannot be grown directly as an economic crop but carry the genetic richness in them. Some of these wild species have attractive plant features with beautiful flowers, fruits and foliage appears unusual from their commercial counterpart. In recent years many of the novel ornamental types from the wild are recognized and domesticated for ornamental gardening, after improving their vegetative and reproductive traits. Therefore, current knowledge on identification, genetic richness, variability, and improvement of non-traditional ornamental species of banana, pomegranate, ginger, pineapple, cabbage, and kale are discussed.